2004
DOI: 10.1002/ijc.20497
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol‐induced in vitro invasion of breast cancer cells: The contribution of MMP‐2 by fibroblasts

Abstract: Ethanol is a tumor promoter and may promote metastasis of breast cancer. However, the underlying cellular/molecular mechanisms remain unknown. Overexpression and high activity of matrix metalloproteinase-2 (MMP-2) are frequently associated with metastatic breast cancers and serve as a prognostic indicator of clinical outcome. MMP-2 is predominantly expressed in stromal fibroblasts and plays a pivotal role in regulating the invasive behavior of breast tumor cells. We hypothesized that ethanol may enhance the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 71 publications
7
57
2
Order By: Relevance
“…Therefore, in stroke brain, rhEPO-enhanced angiogenesis could attract neural progenitor cells via increased MMP2 and MMP9, which may partially explain in vivo findings that rhEPO increases the number of new neurons around the ischemic boundary . Although the MMP inhibitor used in the present study has been shown to block MMP2 activity (Liao et al, 2003;Aye et al, 2004), our results cannot rule out a role for MMP9 in mediating neural progenitor cell migration, and additional studies are warranted.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, in stroke brain, rhEPO-enhanced angiogenesis could attract neural progenitor cells via increased MMP2 and MMP9, which may partially explain in vivo findings that rhEPO increases the number of new neurons around the ischemic boundary . Although the MMP inhibitor used in the present study has been shown to block MMP2 activity (Liao et al, 2003;Aye et al, 2004), our results cannot rule out a role for MMP9 in mediating neural progenitor cell migration, and additional studies are warranted.…”
Section: Discussionmentioning
confidence: 66%
“…For our part, we have postulated that an increase in metalloproteinase expression could be involved in the stimulation of migration observed in breast cancer cells following ethanol exposure. Indeed, it has been recently shown in fibroblasts that ethanol stimulates the secretion of MMP-2 (29), which plays a critical role, together with MMP-9, in extracellular matrix degradation and tumor cell invasion in breast cancer (15,17). Moreover, ethanol activates the estrogen signaling pathway in breast cancer cells (14,21), and some studies show that estrogens are able to stimulate the secretion of MMP-2 and -9 (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study shows that, in fibroblasts, ethanol increases MMP-2 secretion by the protein kinase C pathway (PKC) (29). Nevertheless, TPA, a PKC activator, stimulated the secretion of MMP-9 while it did not change the level of MMP-2 in MCF-7 cells and in organotypic cultures of human breast cancer tissue (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The initial step of breast cancer cell metastasis is characterized by the breakdown of the basement membrane, a process known to be dependent on type IV collagen-degrading enzymes, predominantly MMP-2 and MMP-9 (28). The expression of MMPs, particularly the gelatinases (MMP-2 and MMP-9), has been associated with a high potential of metastasis in several human carcinomas, including breast cancer (29,30 …”
Section: Matrix Metalloproteinases (Mmps)mentioning
confidence: 99%